Punctuation - Prayoga, Raditya; Siti Azizah Rahmah; M. Army Chaniago; Yani Lubis (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
Proficiency in the application of punctuation marks is an essential competency in written literacy that is often neglected in pedagogical discourse within educational institutions. This research aims to investigate the significance of punctuation mechanics in constructing meaning coherence and the effectiveness of message dissemination across various communication platforms. Through a qualitative approach with a descriptive-analytical design, this study synergizes library research of 15 relevant linguistic scientific literatures with qualitative observations of text interaction patterns on social media. The results reveal that typographic symbols such as commas, periods, and exclamation marks are not merely complementary grammatical elements, but pedagogical instruments that function to regulate intonation, idea segmentation, and the reader’s emotio. nal emphasis. Ineptitude in punctuation usage is proven to result in interpretive ambiguity that degrades the quality of writing professionalism and message readability. Furthermore, the dynamics of digital communication have expanded the function of punctuation as a representation of mood in informal interactions. As an educational implication, this study recommends the need for explicit and systematic integration of punctuation instruction into the academic writing curriculum. This is considered crucial to equip students with precise, adaptive, and accountable communication skills amidst rapid information technology developments, aiming to minimize the risk of information misinterpretation in the digital public sphere.